Heavy metals as indicators of parent rocks in a topolithosequence in Triângulo Mineiro, State of Minas Gerais, Brazil - Oliveira, Teogenes Senna de; Costa, Liovando Marciano da; Cruz, Cosme Damião; Horn, Heinrich Adolf (Pesquisa Agropecuaria Brasileira, 1999)
The present study had the purpose to determine the contents of heavy metals in soil samples of a topolithosequence collected in the Triângulo Mineiro, State of Minas Gerais, in order to test the hypothesis that these elements could be used in the identification and separation of the influence of the parent material. The contents of Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn were determined through two types of concentrated acid attack: HNO3/HClO4 (4:1) and HF/HNO3/HClO4 (20:6:3), and dosed by espectrophotometry of atomic absortion. Procedures of multivariated analysis were used for the statistical data evaluation. The results confirm the hypothesis and permitted to conclude that the heavy metals are indicator of the parent material, being able to be used for the separation and delimitation of the area of their influence. The adopted multivariated techniques proved to be viable for this kind of study only when analysed as a whole.